2014
DOI: 10.4321/s0004-05922014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de cordeiros Texel e Ideal alimentados com casca de soja

Abstract: SUMMARYThis experiment was conducted in the laboratory of sheep-raising of the Federal University of Santa Maria aiming to evaluate the ingestive behavior of sheep breeds Texel and Ideal, finished in feedlot with diets containing different levels of soybean hulls in place of sorghum silage. Forty male uncastrated lambs were used, 20 from the Texel breed and 20 from Ideal breed, weaned approximately at 50 days and housed in individual pens were randomly divided into four groups according to the level of inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Chewing time has been one of the most studied measures to evaluate fiber effectiveness (13) . Carvalho et al (16) observed that rumination and chewing time decreased linearly with the increasing replacement of soybean hull by sorghum silage.…”
Section: Resultsmentioning
confidence: 99%
“…Chewing time has been one of the most studied measures to evaluate fiber effectiveness (13) . Carvalho et al (16) observed that rumination and chewing time decreased linearly with the increasing replacement of soybean hull by sorghum silage.…”
Section: Resultsmentioning
confidence: 99%
“…Por outro lado, o valor médio observado para o consumo de FDN de 0,50 kg/dia está de acordo com o verificado por Alves et al (12) , os quais testaram diferentes níveis de energia em dietas para ovinos da raça Santa Inês e observaram um consumo médio de 0,47 kg de FDN/dia, em uma dieta contendo 58,3% de FDN. Baseado nas comparações acima, pode-se afirmar que alimentos com elevado teor de FDN poderão ter sua ingestão restringida e, provavelmente, proporcionar limitação da expressão do potencial genético do animal para produção (13) . Entretanto, no presente estudo, de acordo com os resultados observados e comparados com a literatura, não foram evidenciadas possíveis restrições no consumo de matéria seca, o que permite sugerir que não ocorreu regulação física do consumo dos animais.…”
Section: Resultsunclassified
“…The rumination and chewing time expressed in min/d also differed between CONT and SB, being higher for CONT, which can be attributed to the higher NDF content of this treatment, since the rumination time is highly correlated (r² = 0.96) with the consumption of NDF (Welch and Hooper, 1988). The NDF content of food is one of the main factors that influence the ingestive behavior of animals, with lowers amounts of NDF and/or the smaller particle size, less time will be spent on chewing activity (feeding and rumination ;Carvalho et al, 2014).…”
Section: Ingestive Behaviormentioning
confidence: 99%